Lake and wetland ecosystem services measuring water storage and local climate regulation. Issue 4 (19th April 2017) - Wong, Christina P.; Jiang, Bo; Bohn, Theodore J.; Lee, Kai N.; Lettenmaier, Dennis P.; Ma, Dongchun; Ouyang, Zhiyun
Abstract: Developing interdisciplinary methods to measure ecosystem services is a scientific priority, however, progress remains slow in part because we lack ecological production functions (EPFs) to quantitatively link ecohydrological processes to human benefits. In this study, we tested a new approach, combining a process‐based model with regression models, to create EPFs to evaluate water storage and local climate regulation from a green infrastructure project on the Yongding River in Beijing, China. Seven artificial lakes and wetlands were established to improve local water storage and human comfort; evapotranspiration (ET) regulates both services. Managers want to minimize the trade‐off between water losses and cooling to sustain water supplies while lowering the heat index (HI) to improve human comfort. We selected human benefit indicators using water storage targets and Beijing's HI, and the Variable Infiltration Capacity model to determine the change in ET from the new ecosystems. We created EPFs to quantify the ecosystem services as marginal values [Δfinal ecosystem service/Δecohydrological process]: (1) Δwater loss (lake evaporation/volume)/Δdepth and (2) Δsummer HI/ΔET. We estimate the new ecosystems increased local ET by 0.7 mm/d (20.3 W/m 2 ) on the Yongding River. However, ET rates are causing water storage shortfalls while producing no improvements in human comfort. The shallow lakes/wetlands are vulnerable to drying when inflow rates fluctuate, low depths lead to higher evaporative losses, causing water storage shortfalls with minimal cooling effects. We recommend managers make the lakes deeper to increase water storage, and plant shade trees to improve human comfort in the parks. Key Points: A challenge to measuring ecosystem services is creating ecological production functions linking ecohydrological processes to human benefits Water storage and local climate regulation were evaluated from seven artificial lakes and wetlands in Beijing Lakes and wetlands increased local evapotranspiration causing water storage reductions while providing minimal cooling for human comfort